Écrire un « conte à structure savante » : apparition, métamorphoses et déclin du récit merveilleux-scientifique dans l’œuvre de Maurice Renard (1909-1931) - Fleur Hopkins (ReS Futurae)
This paper examines the merveilleux-scientifique genre (birth, flowering, fall, disparition) of Maurice Renard by leveraging his unprecedented archives. The genre, which appeared in a manifesto-like article in 1909, keeps reshaping itself for almost 20 years et regularly changes its name to try and seduce critics and readers. More than a literary form, the merveilleux-scientific turns out to be, in Renard’s theorical texts, a lever to think about the world and to arouse the reader’s mind.